Teacher Ethics in Installing Student Character Through a Positive Discipline Program - Utami, Hardini Rahmatin; Sulhan, Ahmad; Fitriani, Muhammad Iwan (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to describe teacher ethics in instilling student character through a positive discipline program. This study uses a descriptive qualitative method. Data collection techniques are carried out by observation, documentation and interviews. The sources in this study were the principal and teachers of Pembina Pemenang State Kindergarten, North Lombok. Data were analyzed by data reduction, data presentation, and data verification. The results of the study show that in implementing a positive discipline program, teacher ethics are needed to be good examples for students. One of the methods applied is the implementation of positive discipline through class beliefs. This is considered very effective in forming the character of students who obey the rules, teachers understand that rules must be enforced fairly but also ensure that each student is treated with respect for their dignity such as being willing to listen to students' opinions. By integrating ethical values into everyday education and ensuring that teaching practices reflect equity and diversity, teachers can create a supportive learning environment for all students. Thus, positive discipline programs are not just about enforcing rules, but also about developing strong, positive student character that will have a long-term positive impact on students and society as a whole.